2020
DOI: 10.1073/pnas.1913788117
|View full text |Cite
|
Sign up to set email alerts
|

Aminoacyl-tRNA synthetase inhibition activates a pathway that branches from the canonical amino acid response in mammalian cells

Abstract: Signaling pathways that sense amino acid abundance are integral to tissue homeostasis and cellular defense. Our laboratory has previously shown that halofuginone (HF) inhibits the prolyl-tRNA synthetase catalytic activity of glutamyl-prolyl-tRNA synthetase (EPRS), thereby activating the amino acid response (AAR). We now show that HF treatment selectively inhibits inflammatory responses in diverse cell types and that these therapeutic benefits occur in cells that lack GCN2, the signature effector of the AAR. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 141 publications
(231 reference statements)
0
23
0
Order By: Relevance
“…Indeed, it has long been known that this type of stress can be partially suppressed by the small molecule inhibitors DHP 2, sorafenib, and nilotinib, which target ZAK [297 299]. These findings might also explain recent observation that the cell response to ARSase inhibitors (see above) is dis similar to that induced by regular amino acid starvation [252]. The response to deacylated tRNA and frequent ribosome collisions is based on the activation of GCN2 and/or MAPK stress kinases and occurs via different sce nario than the starvation response, which "senses" amino acids availability through a cascade of interactions involv ing mTOR kinase [300].…”
Section: Ribotoxic Stress and Translation Related Stress Responsesmentioning
confidence: 93%
See 1 more Smart Citation
“…Indeed, it has long been known that this type of stress can be partially suppressed by the small molecule inhibitors DHP 2, sorafenib, and nilotinib, which target ZAK [297 299]. These findings might also explain recent observation that the cell response to ARSase inhibitors (see above) is dis similar to that induced by regular amino acid starvation [252]. The response to deacylated tRNA and frequent ribosome collisions is based on the activation of GCN2 and/or MAPK stress kinases and occurs via different sce nario than the starvation response, which "senses" amino acids availability through a cascade of interactions involv ing mTOR kinase [300].…”
Section: Ribotoxic Stress and Translation Related Stress Responsesmentioning
confidence: 93%
“…Many ARSase inhibitors are of great medical impor tance, as they have the immunosuppressive activity and are extensively used as antimicrobial, antitumor, and antiparasitic agents [239,251]. Their effects on the living cell are usually mediated not only by the suppression of protein synthesis, but also by triggering a special type of stress response [252] caused by the accumulation of dea cylated tRNAs in the cytoplasm and collisions of translat ing ribosomes (see below).…”
Section: Inhibitors Of Aminoacyl Trna Synthetasesmentioning
confidence: 99%
“…Because protein synthesis imposes a significant energy cost on the cell, the amino acid response preserves ATP and GTP, and contributes to the hypometabolic response. GCN2 activation protects the cell from environmental danger [ 93 , 94 ], and contributes to longevity [ 95 ], but at the cost of inhibited healing [ 96 ]. The role of extracellular ATP signaling in the GCN2-on/mTORC1-off mediated amino acid depletion response has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid insu ciency will cause depletion of available aminoacylated tRNA, which is essential for the host to sense amino acid limitation and immune response [33][34][35]. A recent study on several mammalian cell models reported that when aminoacyl-tRNA synthetase was inhibited, the cytokine stimulated proin ammatory response would be substantially suppressed, and a single amino acid depletion, such as arginine or histidine, could also suppress the cytokine induced immune response [36].Thus the identi ed pathways regulating in aminoacyl-tRNA biosynthesis and arginine biosynthesis may be both involved in the in ammatory response. Additionally, arginine and BCAAs (i.e., valine, leucine and isoleucine), were also reported regulating innate and adaptive immune responses and enhancing intestinal development [37].…”
Section: Discussionmentioning
confidence: 99%